2014
DOI: 10.1002/jcla.21751
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Analyzing the Duffy Blood Group Genotype by TaqMan Minor Groove Binding Probes

Abstract: The 5'-NA for genotyping of Duffy blood group is simple, rapid, reliable, reproducible, sensitive, and high-throughput and is superior to PCR-ASP used in routine genotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
2
4
0
Order By: Relevance
“…Duffy blood group allele frequencies in the Thai population and other Asian populations were compared. The observed allele frequencies were similar to those found in Chinese populations [ 17 21 ] and were significantly different from those of Japanese, Korean, and Malaysian populations ( Table 2 ) [ 14 22 23 ].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Duffy blood group allele frequencies in the Thai population and other Asian populations were compared. The observed allele frequencies were similar to those found in Chinese populations [ 17 21 ] and were significantly different from those of Japanese, Korean, and Malaysian populations ( Table 2 ) [ 14 22 23 ].…”
Section: Resultssupporting
confidence: 81%
“…This is the first report of FY blood group allele frequencies in the Thai population. The FY * A allele was the most common and its frequency was similar to that observed in Chinese populations [ 17 21 ]; but it was statistically significantly different ( P <0.05) from that in Korean, Japanese, and Malaysian populations [ 14 22 23 ]. A recent study compared the Kidd blood group allele frequencies in two Thai blood donors [ 26 ], and found that Kidd blood group allele frequencies in Thai individuals were statistically different from those of Japanese individuals, but similar to those of Chinese individuals [ 21 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This assay can be subject to multiplexing, allowing for the simultaneous detection of multiple SNPs in one single reaction (TaqMan Assay, Life Technologies, Carlsbad, CA, USA). Derived methods may also be used, such as the so‐called displacing probes (two allele‐specific probes of different length) and minor groove‐binding probes techniques, both being used for RBC genotyping .…”
Section: Medium‐ To High‐throughput Systemsmentioning
confidence: 99%
“…© 2015 International Society of Blood Transfusion, ISBT Science Series (2015) 10 (Suppl. 1),[31][32][33][34][35][36][37][38] Molecular tools in immunohaematology 35…”
mentioning
confidence: 99%